2022
DOI: 10.4103/ijo.ijo_1281_22
|View full text |Cite
|
Sign up to set email alerts
|

Improving assistive technology access to students with low vision and blindness in Delhi: A school-based model

Abstract: Purpose: Assistive technology (AT) has recently received considerable attention around the world. Studies have shown poor access to assistive technology for visual impairment (ATVI) in schools for the blind in India. The present article aimed at designing a school-based model to improve AT access in schools and provide hands-on training, and identify types of ocular morbidities present among students. Methods: The vision rehabilitation (VR) team of a tertiary eye-care c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Evidence is mounting on the importance of assistive devices, including traditional optical magnifiers, in managing people with low vision and blindness. [ 21 22 23 ] These devices can help to minimize functional limitations and improve independent living skills in a person with vision loss. The study showed that a sizable number of patients have BCVA better than 1/60.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence is mounting on the importance of assistive devices, including traditional optical magnifiers, in managing people with low vision and blindness. [ 21 22 23 ] These devices can help to minimize functional limitations and improve independent living skills in a person with vision loss. The study showed that a sizable number of patients have BCVA better than 1/60.…”
Section: Discussionmentioning
confidence: 99%
“…The detailed methodology, including the estimation of the sample size, sampling technique, was published in the previous paper. [14] However, brie y, this cross-sectional study was conducted in eight districts selected from four different zones of India from November to December 2021. Individuals of all age groups irrespective of health conditions or functional limitations were included in the study.…”
Section: Methodsmentioning
confidence: 99%